Low-threshold lasing in a microcavity of fluorene-based liquid-crystalline polymer blends - Lee, TW; Park, OK; Cho, HN; Kim, DY; Kim, YC (AMER INST PHYSICS, 2003)
We report the lasing characteristics of a microcavity device made of fluorene-based luminescent polymer blends with liquid crystallinity. Poly(2,7-bis(p-stiryl)-9,9'-di-n-hexylfluorene sebacate) (PBSDHFS) and poly(9,9'-di-n-hexyl fluorenediylvinylene-alt-1,4-phenylenevinylene) (PDHFPPV) were used to comprise a binary blend system. We employed the Forster-type energy transfer from a liquid crystalline donor to a non-liquid-crystalline acceptor to obtain a low lasing threshold. The binary blend film of PBSDHFS/PDHFPPV (98/2 by wt) demonstrated a very low-threshold energy (similar to3 nJ/cm(2)/pulse) for microcavity lasing, which is lower than any other values previously reported on the organic or polymeric microcavity devices with metal or dielectric mirrors. This result implies that the liquid crystalline polymer blends could be a good candidate for the gain material of photo and electrically pumped lasing devices. (C) 2003 American Institute of Physics.